PENGARUH PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN SEMAI JATI (Tectona grandis L.f) PADA LAHAN BEKAS TAMBANG POBOYA - Setiawan, Ari; Umar, Husain; Hamzari, Hamzari (Universitas Tadulako, 2019)
Teak (Tectona grandis L.f) is a timber commodity that has a very high economic value. High teak needs are not in line with the ability to procure teak wood which is still low. Teak growth is often hampered by improper growing conditions, especially in former mining areas. Gold mining activities will also cause a decline in soil microbial population, damage to flora and fauna and the production of tailings from these mining activities. This condition needs treatment through fertilizer application. Urea is a nitrogen fertilizer that is needed by plants to stimulate overall growth, especially stems, branches and leaves. The success of a plant does not escape the use of superior, healthy and quality seeds. The research was conducted for three months, namely from June to August 2016 at Poboya, Mantikulore District, Palu City, Central Sulawesi Province. The material used in the implementation of this study was Semai Jati (Tectona grandis L.F) and urea fertilizer. This study used a completely randomized design consisting of 6 treatments and 3 replications, so that there were 18 experimental / observation units. Sidik Ragam analysis was conducted to determine the effect of the treatment that was tried on teak seedlings. Honest Real Test (BNJ) is conducted to see the effect or treatment. The results showed that the treatment of urea fertilizer had a significant effect on the parameters of height increase and the number of teak seedling leaves, while the increase in diameter had no significant effect. The treatment of P1 (2 g / seed) gave the best influence on all parameters added to the teak seedlings observed.Keywords: Urea Fertilizer, Teak Seedlings, KPH, Poboya Mining Mine.